Strategi Pengembangan Desa Wisata Wahana Wanarata di Desa Karangmangu Kecamatan Kroya Kabupaten Cilacap - Zulaihah, Siti; Sutikno, Chamid; Pribadi, Indah Ayu Permana; Amanda, Ariesta; Millata, Chanifia Izza (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
This research examines the Wahana Wanarata Tourism Village Development Strategy in Karangmangu Village, Kroya District, Cilacap Regency. The research method used is qualitative with descriptive analysis. Using primary and secondary data collected through interview observation and documentation. The Strategy Management Theory used is the Fred R. David and Forest R. David (2016) model with the Strategy stages, namely: Strategy formulation, Strategy implementation, and Strategy evaluation. The research results show that the strategy formulation stages in the Wahana Wanarata Tourism Village have been carried out, but there are still several weaknesses in identifying the main needs and challenges faced by the village. At the implementation stage, development efforts have not fully proceeded according to plan, as can be seen from the minimal increase in the number of visitors and obstacles in maintaining the sustainability of the tourist environment. The strategy evaluation stage has also not been carried out optimally, resulting in a lack of feedback that can be used to improve and adjust the strategies that have been implemented. The implementation of development strategies in the Wahana Wanarata Tourism Village has not achieved the expected results. The three stages of the strategy show that there are obstacles in its implementation, so further evaluation and adaptation of the strategy is needed to optimize the potential of this tourist village.